The Effect of CBT Approach Group Counseling in Reduce Online Game Addiction - Husniah, Hafizatul; Irman, Irman; Yulitri, Rina; Leif, Forsblom; Carol, Tuomi (Yayasan Minang Darussalam, 2023)
Junior High School Elementary School students are currently experiencing the problem of high levels of addiction to online games, impacting on academic and non-academic achievements. One technique that is considered appropriate for reducing addiction is through counseling with the CBT approach. This study aims to determine the effect of CBT counseling techniques in reducing online game addiction. The approach used is polytheistic with a pretest-posttest experimental design. The research population is SMPN students with a sample of 10 people. The instrument used in online game addiction scale with t-test data analysis. Based on the results of data analysis, the results obtained were that there was an influence of the CBT approach group counseling in reducing online game addiction. These results are recommended for teachers and practitioners to be able to use CBT counseling techniques to overcome the problem of online game addiction.